2013
DOI: 10.1521/pdps.2013.41.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Psychodynamic Cultural Psychiatry: A New Approach to Teaching Residents

Abstract: This article describes a course, Psychodynamic Cultural Psychiatry, taught to PGY-3 residents at the New York Presbyterian Hospital-Weill Cornell Medical Center that uses psychodynamic theory to help deepen cultural understanding. We (Sandra Park, the instructor for the course, and Elizabeth Auchincloss, the residency training director) developed the class in 2006 in an effort to raise cultural awareness in the residency curriculum. We believe that despite an inherent Western bias, psychodynamic theory can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Trainees’ appreciation of their own background can prepare psychiatrists to respond effectively to the changing configurations of culture, ethnicity, and identity in contemporary health care settings. Furthermore, trainees have specialized cross-cultural psychiatric knowledge and skills, including treatment of refugees and immigrants, socio-cultural variables that influence the assessment and treatment of a wide range of psychiatric conditions, and a comfortable relationship with cultural dynamics that influence both the psychiatrist/patient relationship and collaboration with a wide range of mental health professionals [15,41,60–[62,73,81,89]. A correlation between therapists’ satisfaction with training and consultation, treatment acceptability, and the likelihood to use the treatment in the future was reported [49,103].…”
Section: Recommendationsmentioning
confidence: 99%
“…Trainees’ appreciation of their own background can prepare psychiatrists to respond effectively to the changing configurations of culture, ethnicity, and identity in contemporary health care settings. Furthermore, trainees have specialized cross-cultural psychiatric knowledge and skills, including treatment of refugees and immigrants, socio-cultural variables that influence the assessment and treatment of a wide range of psychiatric conditions, and a comfortable relationship with cultural dynamics that influence both the psychiatrist/patient relationship and collaboration with a wide range of mental health professionals [15,41,60–[62,73,81,89]. A correlation between therapists’ satisfaction with training and consultation, treatment acceptability, and the likelihood to use the treatment in the future was reported [49,103].…”
Section: Recommendationsmentioning
confidence: 99%
“…Numerous studies have identified a variety of factors that influence medication adherence in psychiatric patients [ 6 ] as well as factors associated with adherence/nonadherence within specific disease groups. In the study of patients with schizophrenia, negative attitudes or subjective response to medication, previous nonadherence, and poor therapeutic alliance were associated with nonadherence [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 As poor adherence may lead to disease recurrence, repeated and long-term hospitalization, loss of productivity, increased mortality, extended treatment period, and national economic losses, drug compliance is an important issue from both the quality of life and health economics perspectives. 5 Numerous studies have identified a variety of factors that influence medication adherence in psychiatric patients 6 as well as factors associated with adherence/nonadherence within specific disease groups. In the study of patients with schizophrenia, negative attitudes or subjective response to medication, previous nonadherence, and poor therapeutic alliance were associated with nonadherence.…”
Section: Introductionmentioning
confidence: 99%